An Evaluation of Sensor and Data Fusion Technologies for Application within an Integrated Base Defence System - Tsourdos, Antonios; Silson, P.; White, B.; Spillings, J.; Burke, P. (Cranfield University, 2009)
The purpose of this paper is to communicate the technical issues involved in integrating data fusion technologies in the development of an integrated base defence system. Options are presented, with possible alternatives, when selecting the sensor systems to support specific mission goals. The document then provides a proposed candidate system architecture that integrates the independent systems to support the commander’s information needs.
Keywords: Signal processing; Multisensor data fusion - Mathematical models; Information theory in mathematics; Multisensor data fusion; Civil defense; Microelectromechanical systems; Sensor technology and devices